g-C3N4–Co3O4 Z-Scheme Junction with Green-Synthesized ZnO Photocatalyst for Efficient Degradation of Methylene Blue in Aqueous Solution - Mintesinot Tamiru Mengistu; Tadele Hunde Wondimu; Dinsefa Mensur Andoshe; Jung Yong Kim; Osman Ahmed Zelekew; Fekadu Gashaw Hone; Newaymedhin Aberra Tegene; Noto Susanto Gultom; Ho Won Jang (Bioinorganic Chemistry and Applications)
A simple wet chemical ultrasonic-assisted synthesis method was employed to prepare visible light-driven g-C3N4-ZnO-Co3O4 (GZC) heterojunction photocatalysts. X-ray diffraction (XRD), scanning electromicroscopy (SEM), Fourier-transform infrared spectroscopy (FTIR), Brunauer–Emmett–Teller (BET), ultraviolet (UV), and electrochemical impedance spectroscopy (EIS) are used to characterize the prepared catalysts. XRD confirms the homogenous phase formation of g-C3N4, ZnO, and Co3O4, and the heterogeneous phase for the composites. The synthesized ZnO and Co3O4 by using cellulose as a template show a rod-like morphology. The specific surface area of the catalytic samples increases due to the cellulose template. The measurements of the energy band gap of a g-C3N4-ZnO-Co3O4 composite showed red-shifted optical absorption to the visible range. The photoluminescence (PL) intensity decreases due to the formation of heterojunction. The PL quenching and EIS result shows that the reduction of the recombination rate and interfacial resistance result in charge carrier kinetic improvement in the catalyst. The photocatalytic performance in the degradation of MB dye of the GZC-3 composite was about 8.2-, 3.3-, and 2.5-fold more than that of the g-C3N4, g-C3N4-ZnO, and g-C3N4-Co3O4 samples. The Mott–Schottky plots of the flat band edge position of g-C3N4, ZnO, Co3O4, and Z-scheme g-C3N4-ZnO-Co3O4 photocatalysts may be created. Based on the stability experiment, GZC-3 shows greater photocatalytic activity after four recycling cycles. As a result, the GZC composite is environmentally friendly and efficient photocatalyst and has the potential to consider in the treatment of dye-contaminated wastewater.